1992
DOI: 10.1182/blood.v80.4.891.bloodjournal804891
|View full text |Cite
|
Sign up to set email alerts
|

Polycythemia vera. II. Hypersensitivity of bone marrow erythroid, granulocyte-macrophage, and megakaryocyte progenitor cells to interleukin-3 and granulocyte-macrophage colony-stimulating factor

Abstract: Polycythemia vera (PV) is a clonal disease of the hematopoietic stem cell characterized by a hyperplasia of marrow erythropoiesis, granulocytopoiesis, and megakaryocytopoiesis. We previously reported that highly purified PV blood burst-forming units-erythroid (BFU-E) are hypersensitive to recombinant human interleukin-3 (rIL-3). Because these cells may be only a subset, and not representative of marrow progenitors, we have now studied partially purified marrow hematopoietic progenitor cells. Dose-response expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 0 publications
2
27
0
2
Order By: Relevance
“…This phenomenon is explained by the increased sensitivity of the pathological progenitor cells to EPO (Casadevall et al, 1982;Weinberg et al, 1989). The same phenomenon was also observed after addition of a cytokine cocktail, confirming the hypersensitivity of the affected progenitor cell to other cytokines including interleukin (IL) 1, IL-3, stem cell factor, insulin-like growth factor-1 and granulocyte-macrophage colony-stimulating factor (Dai et al, 1991(Dai et al, , 1992Correa et al, 1994;Dai et al, 1994).…”
Section: Discussionsupporting
confidence: 57%
“…This phenomenon is explained by the increased sensitivity of the pathological progenitor cells to EPO (Casadevall et al, 1982;Weinberg et al, 1989). The same phenomenon was also observed after addition of a cytokine cocktail, confirming the hypersensitivity of the affected progenitor cell to other cytokines including interleukin (IL) 1, IL-3, stem cell factor, insulin-like growth factor-1 and granulocyte-macrophage colony-stimulating factor (Dai et al, 1991(Dai et al, , 1992Correa et al, 1994;Dai et al, 1994).…”
Section: Discussionsupporting
confidence: 57%
“…In myeloproliferative disorders, it has been suggested that hematopoietic progenitor cells are hypersensitive to certain cytokines: erythroid progenitors to erythropoietin and interleukin-3(IL-3) in polycythemia vera [4,5]; myeloid and megakaryocyte progenitors to IL-3 and granulocyte-macrophage colony-stimulating factor (GM-CSF) in polycythemia vera [6]; myeloid progenitors to GM-CSF in juvenile chronic myeloid leukemia [7]. In ET, Kobayashi et al previously reported megakaryocyte progenitors are hypersensitive to IL-3 [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have shown that, apart from erythropoietin and IGF-1, PV cells are hypersensitive to hematopoietic growth factors including interleukin-3, granulocyte/monocyte colony stimulating factor (GM-CSF), stem cell factor (SCF) and thrombopoietin [54±57]. Dai et al have shown that erythroid colony forming cells from PV bone marrow are up to 100-fold more sensitive to interleukin-3 than normal cells in serum-containing medium [54,55]. Likewise, in the same system, PV BFU-E are 48 times more sensitive to GM-CSF than their normal counterparts [55].…”
Section: P V C E L L S a R E E R Y T H R O P O I E T I N -I N D E P Ementioning
confidence: 99%